Feeder‐independent canine induced pluripotent stem cells maintained under serum‐free conditions. Issue 4 (13th March 2017) - Nishimura, Toshiya; Hatoya, Shingo; Kanegi, Ryoji; Wijesekera, Daluthgamage Pasty Himali; Sanno, Kousuke; Tanaka, Erina; Sugiura, Kikuya; Hiromitsu Tamada, Noritoshi Kawate; Imai, Hiroshi; Inaba, Toshio
Abstract : Canine induced pluripotent stem cells (ciPSCs) are an attractive source for regenerative veterinary medicine, and may also serve as a disease model for human regenerative medicine. Extending the application of ciPSCs from bench to bedside, however, requires resolving many issues. We generated ciPSCs expressing doxycycline‐inducible murine Oct3/4 ( Pou5f1 ), Sox2, Klf4, and c‐Myc, which were introduced using lentiviral vectors. The resultant ciPSCs required doxycycline to proliferate in the undifferentiated state. Those ciPSC colonies exhibiting basic fibroblast growth factor (bFGF)‐dependent proliferation were dissociated into single cells for passaging, and were maintained on a Matrigel‐coated dish without feeder cells in a serum‐free medium. The established ciPSCs had the ability to differentiate into three germ layers, via formation of embryoid bodies, as well as into cells expressing the same markers as mesenchymal stem cells. These ciPSCs may thus serve as a suitable source of pluripotent stem cell lines for regenerative veterinary medicine, with fewer concerns of contamination from unknown animal components.